Pengembangan Wisata Halal di Pulau Pahawang, Kabupaten Pesawaran, Provinsi Lampung - Heru Wahyudi; Tri Puji Wahyuningsih; Widia Anggi Palupi; HERU WAHYUDI (I-Finance Journal, 2022)
This study aims to analyze the potential for developing halal tourism on Pahawang Island. The analytical method used in this study is the SWOT analysis approach, Internal Factor Evaluation (IFE), and External Factor Evaluation (EFE). The results of the study show that the strategies used to develop halal tourism on Pahawang Island include making halal tour packages to attract Muslim tourists and foreign tourists, working with the ministry of tourism to create a halal certification system for tourism businesses on Pahawang Island, and developing product differentiation with tourist attractions. local wisdom-based sharia that is different and unique compared to other sharia tourist destinations in Indonesia. In conclusion, there are 18 strategies for developing halal tourism areas on Pahawang Island, Pesawaran Regency. In addition, internal and external evaluations were also obtained which contributed to the development of halal tourism on Pahawang Island. The contribution of this research resulted in suggestions for local governments, especially the Tourism Office of Pesawaran Regency.